Case report: Treatment with ensartinib shows good response to SQSTM1-ALK fusion in lung adenocarcinoma - Wang, Pandeng; Jiang, Zhuo; Guo, Jianji; Liu, Tao; Liu, Zhen; Wang, Dongdong; Li, Honglin (Frontiers in Pharmacology, 2024)
Lung cancer is a prevalent malignancy, with the rearrangement of the anaplastic lymphoma kinase (ALK) gene being responsible for a minority of cases of non-small cell lung cancer (NSCLC). NSCLC patients harboring ALK fusion proteins demonstrate sensitivity to ALK tyrosine kinase inhibitors (TKIs). In this report, we describe the case of a female patient with metastatic lung adenocarcinoma, identified through NGS to carry a rare inverted SQSTM1-ALK (S5, A20) fusion. The patient received ensartinib as first-line therapy, resulting in a partial response (PR). At the time of publication, the patient’s condition remained favorable. We have, for the first time, identified the presence of SQSTM1-ALK fusion in pericardial effusion, with the favorable response to ensartinib validating the oncogenic potential of SQSTM1-ALK fusion. The substantial advancements and extensive utilization of NGS have facilitated the identification of rare fusion variants.